Proses Produksi di Pabrik Tabung Elpiji - Septivani, Nike (Bina Nusantara University, 2012)
Currently the use of liquefied petroleum gas is urgently needed as a substituting fuel in both household sector and industrial sector. The Government’s program namely the conversion of kerosene to LPG encouraged people who still use kerosene as a fuel to switch to LPG. There are some public complaints about the quality of the conversion product such as conflagration that occurs frequently caused by the explosion of LPG tube. Application of SNI LPG tube related to the energy conversion program is expected to give a safer condition to the users. This study is conducted by analyzing the quality requirement of LPG tube products according to SNI as well as to identify the fulfillment of LPG tube products.